The Effect of the Team Games Tournament (TGT) Learning Model on Students' Achievement in Economics Education - Nofriansyah, Nofriansyah; Wardiman, Jery; Rahmi, Yuri (Journal of Economics and Economic Education, 2024)
This study aims to examine the effectiveness and impact of the Team Games Tournament (TGT) learning model on economics education. The research method used in this article is a literature review. This review aims to analyze and summarize the findings of previous studies, as well as relevant theories related to the application of the Team Games Tournament (TGT) learning model in economics education. This approach was chosen to gain a deeper understanding of the effectiveness, potential, and challenges of the TGT model in improving learning outcomes, motivation, and critical thinking skills in economics education. Data collection was carried out by identifying and gathering journal articles, books, research reports, and other academic sources related to the application of the TGT learning model. This study shows that the Team Games Tournament (TGT) learning model positively impacts economics education at the secondary school level by enhancing student motivation, engagement, and understanding of economic concepts through an enjoyable collaborative approach, while also supporting the development of social skills such as teamwork, communication, and responsibility. This fills the gap in previous research and provides practical guidance for teachers to implement TGT as an interactive and student-centered alternative methods.